Dexaminidae - Myers, Alan A.; Lecroy, Sara E. (Zootaxa, 2009)
Four genera and 11 species of dexaminids are reported from the Great Barrier Reef. Of these, three species (Dexaminoculus grobbeni (Spandl, 1923), Guernea ipilya Thomas & Barnard, 1991, G. yamminye Thomas & Barnard, 1991) have been previously encountered on the Reef, seven species (six Paradexamine, one Polycheria) are new to science and one species (Paradexamine micronesicus Ledoyer, 1979) is reported for the first time from Australian waters. All species are described and illustrated.